Cactacea fruits in native forests of northwestern Argentina: a new option for functional foods - Zampini, Iris Catiana (2011)
Fruits are known as good sources of phytochemicals, essential to prevent degenerative diseases like cancer and cardiovascular diseases. Comparative studies between the antioxidant activity (AOA) and nutritional properties of hydrophilic preparations of four Cactaceae Lepismium lorentzianum (Griseb.) Lepismium lumbricoides (Lem.) Rhipsalis floccosa tucumanensis (F.A.C.Weber) Pfeiffera ianthothele Weber that grown in Argentineum Yunga were performed. L. lumbricoides and L. lorentzianum had the highest sugar content. All fruits accumulated reducing sugars (glucose and fructose). The protein content was 1.5 to 5 mg / g fresh fruit. L. lorentzianum showed more phenolic compounds content. All fruits showed antioxidant capacity, however, L. lorentzianum had the highest antiradical capacity (SC50 = 2.4 mg / ml) and this activity was similar in all forms of extraction (with and without heating). There was a positive correlation between the AAO and the phenolic content of fruits. Conclusions: The fruits of epiphytic cacti of the Yungas Tucumán, would be a new option for functional foods to promote health and prevent diseases related to oxidative stress.